4x(3x-1)-6(2x+1)=

Simple and best practice solution for 4x(3x-1)-6(2x+1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x(3x-1)-6(2x+1)= equation:


Simplifying
4x(3x + -1) + -6(2x + 1) = 0

Reorder the terms:
4x(-1 + 3x) + -6(2x + 1) = 0
(-1 * 4x + 3x * 4x) + -6(2x + 1) = 0
(-4x + 12x2) + -6(2x + 1) = 0

Reorder the terms:
-4x + 12x2 + -6(1 + 2x) = 0
-4x + 12x2 + (1 * -6 + 2x * -6) = 0
-4x + 12x2 + (-6 + -12x) = 0

Reorder the terms:
-6 + -4x + -12x + 12x2 = 0

Combine like terms: -4x + -12x = -16x
-6 + -16x + 12x2 = 0

Solving
-6 + -16x + 12x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-3 + -8x + 6x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-3 + -8x + 6x2)' equal to zero and attempt to solve: Simplifying -3 + -8x + 6x2 = 0 Solving -3 + -8x + 6x2 = 0 Begin completing the square. Divide all terms by 6 the coefficient of the squared term: Divide each side by '6'. -0.5 + -1.333333333x + x2 = 0 Move the constant term to the right: Add '0.5' to each side of the equation. -0.5 + -1.333333333x + 0.5 + x2 = 0 + 0.5 Reorder the terms: -0.5 + 0.5 + -1.333333333x + x2 = 0 + 0.5 Combine like terms: -0.5 + 0.5 = 0.0 0.0 + -1.333333333x + x2 = 0 + 0.5 -1.333333333x + x2 = 0 + 0.5 Combine like terms: 0 + 0.5 = 0.5 -1.333333333x + x2 = 0.5 The x term is -1.333333333x. Take half its coefficient (-0.6666666665). Square it (0.4444444442) and add it to both sides. Add '0.4444444442' to each side of the equation. -1.333333333x + 0.4444444442 + x2 = 0.5 + 0.4444444442 Reorder the terms: 0.4444444442 + -1.333333333x + x2 = 0.5 + 0.4444444442 Combine like terms: 0.5 + 0.4444444442 = 0.9444444442 0.4444444442 + -1.333333333x + x2 = 0.9444444442 Factor a perfect square on the left side: (x + -0.6666666665)(x + -0.6666666665) = 0.9444444442 Calculate the square root of the right side: 0.971825316 Break this problem into two subproblems by setting (x + -0.6666666665) equal to 0.971825316 and -0.971825316.

Subproblem 1

x + -0.6666666665 = 0.971825316 Simplifying x + -0.6666666665 = 0.971825316 Reorder the terms: -0.6666666665 + x = 0.971825316 Solving -0.6666666665 + x = 0.971825316 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.6666666665' to each side of the equation. -0.6666666665 + 0.6666666665 + x = 0.971825316 + 0.6666666665 Combine like terms: -0.6666666665 + 0.6666666665 = 0.0000000000 0.0000000000 + x = 0.971825316 + 0.6666666665 x = 0.971825316 + 0.6666666665 Combine like terms: 0.971825316 + 0.6666666665 = 1.6384919825 x = 1.6384919825 Simplifying x = 1.6384919825

Subproblem 2

x + -0.6666666665 = -0.971825316 Simplifying x + -0.6666666665 = -0.971825316 Reorder the terms: -0.6666666665 + x = -0.971825316 Solving -0.6666666665 + x = -0.971825316 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.6666666665' to each side of the equation. -0.6666666665 + 0.6666666665 + x = -0.971825316 + 0.6666666665 Combine like terms: -0.6666666665 + 0.6666666665 = 0.0000000000 0.0000000000 + x = -0.971825316 + 0.6666666665 x = -0.971825316 + 0.6666666665 Combine like terms: -0.971825316 + 0.6666666665 = -0.3051586495 x = -0.3051586495 Simplifying x = -0.3051586495

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.6384919825, -0.3051586495}

Solution

x = {1.6384919825, -0.3051586495}

See similar equations:

| 3/10=-8/5-n | | 30/7x=-255/28 | | sec(2x)+tan(x)=1 | | a-(-16)=11 | | 5c^3-15c^2+10c=0 | | 3r+9=-3(8r-3) | | 3r+9=24+9 | | 7+15x+2x^2= | | log(5)(5x+6)=2 | | tanx=cotx | | 0.5r+7=9 | | -4c+4c-2= | | -5(7r+5)=31-7r | | 5x^2-2x-16=2x^2+6x | | 2cos(2x)-cos(x)=0 | | logx+2(0)16=4 | | 7r^2-19r-14=-3r+1 | | 30x^2-20x-28=5x^2+4 | | X/2=62 | | V/2=62 | | 3x(-7x^4y)= | | 25n^2+4n-1=1-5n^2 | | 1.13=ln(x/1) | | -6(8-8p)-7=-15+8p | | 25n^2+4n-1=1-5n | | 1-6(-8k-2)=109 | | 8y+96=3y-9 | | x=23000-(x(.12))+(x(.05)) | | 2m+5=8 | | a+14=17 | | x=23-(x(.12))+(x(.05)) | | log(x)+log(x^4)=5 |

Equations solver categories